Comparative research on nucleocapsid and spike glycoprotein as the rapid immunodetection targets of COVID-19 and establishment of immunoassay strips. (March 2021) - Liu, Dan; Wu, Feng; Cen, Yu; Ye, Lei; Shi, Xueyin; Huang, Yulan; Fang, Shisong; Ma, Lan
Highlights: The monoclonal antibodies against S protein of COVID-19 have cross-reaction with HCoV-OC43, HCoV-NL63 and HCoV-HKU1. The N protein Ag-mAb system is more specific and accurate, suitable for immunoassay. N protein strips we prepared can quickly and easily screen the swab samples within 11 min with 93.33 % accuracy rate. Abstract: The SARS-CoV-2 virus responsible for coronavirus 2019 (COVID-19) poses a significant challenge to healthcare systems worldwide. According to the World Health Organization (WHO), the outbreak of COVID-19 has been a pandemic that infected more than 25.32 million people and caused more than 848.25 thousand deaths worldwide at the time of 1st September 2020. Despite governmental initiatives aimed to contain the spread of the disease, several countries are experiencing unmanageable increases in medical equipment and larger testing capacity. The current diagnosis based on nuclear acid requires specialized instruments, time-consuming, and laborious, the low-cost and convenient technologies were still urgently needed. Both spike and nucleocapsid are key structural proteins of COVID-19 with good immunogenicity, can serve as primary targets for immunoassay. After comparative research, we certified nucleocapsid antigen-monoclonal antibody (mAbs) system was more suitable for the COVID-19 immunodetection. Subsequently, we designed a rapid test strip based on it that can be used in large-scale screening of COVID-19 in population and more suitable for some remote and special needs areas were restricted by a medical condition or for quick and large quantities of screenings.